Huckleberry finn - Brook, Henry; McNee, Ian Twain, Mark (Usborne London, 2014)
Mark Twain''s classic tale of Huckleberry Finn's escape and adventure down the Mississippi river rivetingly retold for today's readers. Clearly written in a modern, approachable style, Classics Retold are designed to introduce young readers to much-loved classic stories